Acute compartment syndrome and fasciotomy after a viper bite in Italy: a case report - Marco Sassoè-Pognetto; Riccardo Cavalcante; Matteo Paonessa (BMC, 2024)
Abstract Background Bites caused by European vipers are rare medical emergencies but can occasionally cause life-threatening complications. Viper venom causes local symptoms, which can be accompanied by systemic manifestations in severe cases. The local effects of snakebites include edema and, more rarely, necrosis and compartment syndrome. The consequences of envenomation are often more pronounced in children due to their smaller body size. Case presentation We present the case of a 6-year-old girl who experienced multiple viper bites in the lower limb in northwest Italy. The girl received supportive care but progressed to develop compartment syndrome that required emergency fasciotomy. The patient's condition improved promptly after surgical decompression and administration of antivenom, but full recovery required prolonged hospitalization and rehabilitation. Conclusions This case highlights the importance of obtaining a timely assessment of the severity of viper envenomation without delaying the administration of antivenom in most serious cases. The presence of multiple bite marks on the patient is one factor that may help to predict the clinical severity of snakebites and anticipate symptom progression.